The development and disintegration of a Classic Maya center and its climate context. (April 2023) - Prufer, KM; Thompson, AE; Wickert, AD; Kennett, DJ
Research in Southern Belize has produced a 1000-year record of coupled human and environmental relationships at the ancient Maya city Uxbenká. Located at the southeastern margin of the Maya Lowlands, this region has excellent agricultural land and some of the highest rainfall in the Maya region. Uxbenká was the founding political center in southern Belize after 100 BCE. After 850 years, Uxbenká experienced a long geopolitical disintegration ending in depopulation as part of broad regional collapse. We use kernel density and summed probability distributions of 167 high-precision AMS 14 C dates to reconstruct relative changes in population and investments in the built environment throughout the growth and decline of the polity. Those data are compared to an annually resolved speleothem paleoclimate record from Yok Balum cave, located less than 3 km from Uxbenká's civic ceremonial core. With no Classic Period wetland fields or evidence for large-scale landscape investments in agricultural intensification, food production would have been rainfall dependent as was water availability for household use. Using a 30 m SRTM DEM, we compute flow accumulation and the upvalley extents of river networks while varying the input precipitation to reflect hypothesized changes in paleorainfall over time. Our data suggest that Uxbenká experienced rapid growth following a severe drought at 200 CE, as well as cycles of growth and contraction until just after 750 CE. We find that geopolitical disintegration in southern Belize was already underway when a severe drought began at 830 CE. That six-decade drought likely contributed to the abandonment of Uxbenká and limited geopolitical reorganization.